PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PROYEK KONSTRUKSI GEDUNG KEJAKSAAN TINGGI KALIMANTAN TIMU - Habir Habir; Nanda Mardianti (Prodi Ilmu Administrasi Negara, 2022)
In Indonesia, the construction industry development that is being carried out requires the guarantee of Manpower Safety and Health which is very important, which means protecting workers from the risk of work accidents. In this day and age, things like work safety are often underestimated because they are considered to only waste time and costs. Construction work has distinctive properties, including in open spaces that are affected by weather, limited work periods, using untrained workers, using work equipment that endangers occupational safety and health, and work that expends a lot of energy, especially in high-rise buildings, is a busy job of activities with a high level of risk.The research method is carried out using observation, interviews, and the distribution of questionnaires. A study, of course, must have the basics of discussion of an object to be studied, this is very related to the data that will be collected to support the results of the research. Based on the results of the study, it can be concluded as follows: The results of the analysis of the implementation of the Occupational Safety and Health Management System (SMK3) from 30 respondents (Based on worker involvement, as many as 22.97% of respondents chose to simply apply and 74.07% chose to be applied, the Management Role chosen by respondents with the category of sufficiently applying as much as 42.2% and 57.8% of smk3, K3 regulations and procedures chosen by respondents with the category of knowing the regulations and K3 procedures and carrying out K3 activities at the project site by 20% chose to simply apply and 80% chose to be applied, Based on Working Conditions and Environment as many as 80% of respondents chose to simply apply and 20% chose to apply K3 at the Project site. The results of the analysis of the availability of K3 supporting facilities are as follows: ( For the completeness of the helmet of 80% available, feasible, but incomplete and 20% available, feasible and complete, Completeness of safety shoes 66.70% available, feasible, but incomplete and 33.30% available, feasible and complete, Completeness of gloves by 100% which is available, feasible, and complete at the project site, Completeness of vests of 80% that is available, feasible, but less complete and 20% available, feasible and complete, Completeness of Masks of 100% which are available, feasible and complete, Completeness of Safety Glasses of 93.33% available, feasible and incomplete and incomplete and 6.67% available, feasible and complete, Welding gloves of 66.66% available, feasible, but less complete and 6.68% available, feasible, and complete, For completeness, body harness, Ear Plugs, Face Shields and Boat Shoes have the same percentage result, which is 66.70% available, feasible, but less complete, and 33.30% available, decent and complete